DEFORESTATION AND ITS EFFECTS ON LOCAL CLIMATE PATTERNS: AN ANALYTICAL STUDY - Rifat Khursheed (CV. Radja Publika, 2025)
Deforestation is a significant environmental issue that disrupts ecosystems, alters climate patterns, and contributes to global warming. This study examines the impact of deforestation on local climate patterns, focusing on temperature variations, precipitation changes, and shifts in humidity levels. Using case studies from tropical and temperate regions, the paper highlights the link between forest loss and climatic changes. The findings suggest that deforestation intensifies local warming, disrupts precipitation cycles, and exacerbates extreme weather events. The study underscores the urgency of implementing sustainable forest management practices to mitigate these adverse effects.